Pengaruh Kepuasan Kerja Dan Komitmen Organisasi Terhadap Organizational Citizenship Behavior Serta Dampaknya Terhadap Kualitas Pelayanan Pada Universitas X di Kota Bandung - Lenni Lukitasari (Jurnal Ekonomi, Bisnis & Entrepreneurship, 2018)
This study aims to determine and analyze the permanent lecturer job satisfaction of the University of X in the city of Bandung, permanent lecturer organizational commitment of the University of X in Bandung, a permanent lecturer at University X in Bandung, service quality at the University of X in Bandung. Organizational Citizenship Behavior, the magnitude of the influence of organizational commitment on Permanent Organizational Citizenship Behavior of University X in Bandung, the influence of Organizational Citizenship Behavior on the Quality of Service and the influence of job satisfaction and organizational commitment on the quality of University services X in the city of Bandung. This research conducted at the University of X in the city of Bandung. The population in this study were 64 Permanent Lecturers at the Faculty of Economics, University of Bandung.Based on the purpose of the research to be carried out, the research method used is descriptive analysis to describe the nature of something and examine the causes of a particular phenomenon and answering questions concerning something at the time of the ongoing research process. The analysis used is path analysis and using the SPSS program. Based on the results of the study, it appears that job satisfaction has a direct influence of 20.34%, the indirect effect of job satisfaction through organizational commitment is 12.43%, so the total effect of job satisfaction is 32.77%. Organizational commitment has a direct influence of 27.14%, the indirect effect of organizational commitment through job satisfaction is 12.43%, so the total influence of organizational commitment is 39.57%. The overall total effect is 72.34%. The effect of other factors not examined on Organizational Citizenship Behavior is indicated by the value = 0.2766 or 27.66% and the magnitude of the influence of Organizational Citizenship Behavior on service quality is 75.3%, the effect of other factors not examined on service quality is indicated by the value = 0.247 or equal to 24.7%.